2018
DOI: 10.5812/semj.64056
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Strategy Map to Improve Public Hospitals Performance with Balanced Scorecard and DEMATEL Approach

Abstract: Background: The hospital is a significant part of health systems that presents a complex and vital services. Therefore, performance management of hospitals should be considered especially. BSC model is so helpful and popular for performance management. In using BSC, cause and effect relations is very important, since it helps to apply non-financial to forecast financial performance. Objectives: This study aims to analysis systematic relations between key indicators of hospital performance evaluation, identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Findings indicated that the micro environmental factors affected the quality of services as well as their expenditures. One of the key micro factors is the lengthy waiting time (as indicated in Table 1), impacting the efficiency, effectiveness and customer satisfaction [20][21][22][23]. The results of a meta-analysis by Fazel Hashemi et al showed that this indicator was higher in the emergency departments of Iranian hospitals in comparison with national and international standards.…”
Section: Discussionmentioning
confidence: 99%
“…Findings indicated that the micro environmental factors affected the quality of services as well as their expenditures. One of the key micro factors is the lengthy waiting time (as indicated in Table 1), impacting the efficiency, effectiveness and customer satisfaction [20][21][22][23]. The results of a meta-analysis by Fazel Hashemi et al showed that this indicator was higher in the emergency departments of Iranian hospitals in comparison with national and international standards.…”
Section: Discussionmentioning
confidence: 99%
“…Hamed Rahimi et al, (2017) analyzed systematic relations between key indicators of hospital performance evaluation, identifying causal relations and prioritizing indicators based on the 4 perspectives described by the balanced scorecard (BSC).…”
Section: Literature Surveymentioning
confidence: 99%
“…Moreover, the results obtained by Etzkowitz showed that the goals of entrepreneurial universities will be realized when the results and achievements of some particular research or innovation are revealed. In addition, it was noted that value-adding occurs by the university itself operating the result of the research or innovation (22).…”
Section: Fourth Scenario: Alert For Moving Backward To First-generatimentioning
confidence: 99%